Posterior Lissencephaly Associated with Subcortical Band Heterotopia Due to a Variation in the CEP85L Gene: A Case Report and Refining of the Phenotypic Spectrum - Gianluca Contrò (Genes, 2021)
Lissencephaly describes a group of conditions characterized by the absence of normal cerebral convolutions and abnormalities of cortical development. To date, at least 20 genes have been identified as involved in the pathogenesis of this condition. Variants in CEP85L, encoding a protein involved in the regulation of neuronal migration, have been recently described as causative of lissencephaly with a posterior-prevalent involvement of the cerebral cortex and an autosomal dominant pattern of inheritance. Here, we describe a 3-year-old boy with slightly delayed psychomotor development and mild dysmorphic features, including bitemporal narrowing, protruding ears with up-lifted lobes and posterior plagiocephaly. Brain MRI at birth identified type 1 lissencephaly, prevalently in the temporo–occipito–parietal regions of both hemispheres with “double-cortex” (Dobyns’ 1–2 degree) periventricular band alterations. Whole-exome sequencing revealed a previously unreported de novo pathogenic variant in the CEP85L gene (NM_001042475.3:c.232+1del). Only 20 patients have been reported as carriers of pathogenic CEP85L variants to date. They show lissencephaly with prevalent posterior involvement, variable cognitive deficits and epilepsy. The present case report indicates the clinical variability associated with CEP85L variants that are not invariantly associated with severe phenotypes and poor outcome, and underscores the importance of including this gene in diagnostic panels for lissencephaly.